Accumulation of an Intermediate in DNA Synthesis by HEp.2 Cells Treated with Methyl Methanesulfonate - Kato, Karen (1974)
A portion of the DNA synthesized by HEp.2 cells after short incubation in the presence of BrdU bands in a CsCl gradient at a distinct peak of density 1.715-1.718 g/cm(3). Inhibition of DNA synthesis by methyl methanesulfonate results in an increased proportion of this “intermediate density” DNA. Cells labeled and subsequently chased in nonradioactive BrdU yield only hybrid DNA. Treatment with single-strand-specific deoxyribonuclease converts a portion of the intermediate density material to molecules of hybrid density (1.755 g/cm(3)). The data suggest an intermediate in DNA replication that contains a single-stranded region in the parental strand and that accumulates when DNA synthesis is blocked by an alkylation-induced lesion.